Estimation of Traffic Demand: classic, tour- based and activity-based models. (Review) - Coto-Solano, María Estefanía (2019)
Transportation models are representations of traffic networks through the application of mathematical methods and theoretical concepts. The level of detail included in these models determines the precision and realism with which behavior of people’s mobility is calculated. To choose a model, traffic estimation developers shall define previously the scope, precision needed and human and economic resources available. Improvements in transportation models have been the reserve of theory. It is necessary to expand this knowledge to field professionals for its practical application. In this article, a review of three transportation models widely used in the world is presented. This is intended so that those in charge of demand estimation can benefit from the review of the advantages and limitations of frequently used transportation models.